Influence of "productive" Impurities (Cd, Na, O) on the Properties of the Cu2ZnSnS4Absorber of Model Solar Cells - Sergeyev, D.; Zhanturina, N.; Aizharikov, A.; Popov, Anatoli I. (Walter de Gruyter, 2021)
Abstract The study focuses on the optical properties of the CZTS multicomponent semiconductor absorber with 3 % "production"impurities of Cd, Na, O within the framework of the density functional theory using the generalized gradient approximation and the SCAPS program, as well as investigates their influence on the performance and efficiency of CZTS-solar cells. The results showed that the introduction of Cd, Na, O impurities would lead to a decrease in the intensity of the absorption bands at 2.06 eV and 2.55 eV. The density of states CZTS: (Cd, Na, O) was determined from first principles, and it was revealed that impurities of Cd and O atoms would lead to a decrease in the band gap (to 0.9 eV and 0.79 eV), and an increase in Na impurity absorption (1.2 eV). It was also found that a decrease in the band gap led to a decrease in the open circuit voltage, and it was also shown that "industrial"impurities led to a decrease in the efficiency of energy conversion of solar cells to 2.34 %. © 2021 D. Sergeyev et al., published by Sciendo. This work is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License.
The research has been supported by grant of the Ministry of Education and Science of the Republic of Kazakhstan AP09562784. The authors (D. Sergeyev) acknowledges the provision of SCAPS-1D software by Prof. Marc Burgelman. The research of A.I. Popov has been supported by the Institute of Solid State Physics (ISSP), University of Latvia (UL). ISSP UL as the Centre of Excellence is supported through the Framework Program for Euro-pean Universities Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2 under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES; Cu2ZnSnS4(CZTS); density of states; JV-characteristics; optical absorption coefficient; SCAPS; solar cell